Marxism and historical writing - Hirst, Paul Q. (Routledge, 2017)
In this reissued collection of essays, first published in 1985, Paul Q. Hirst assesses the limits of the Marxist theory of history in its various versions. It begins with an extended critical discussion of Perry Anderson and Edward Thompson, and includes chapters on G.A Cohenâe(tm)s attempt to re-state the Marxist theory of history in terms compatible with analytic philosophy, on R.G. Collingwoodâe(tm)s theory of history, on Andersonâe(tm)s work on Absolutism, on Thompsonâe(tm)s Poverty of Theory, and on the contemporary politics of democratic socialism.